The Evaluation of Antioxidant Activities and Phenolic Compounds in Leaves and Inflorescence of Artemisia dracunculus L. by HPLC - J Khezrilu Bandli; R Heidari (Institue of Medicinal Plants, ACECR, 2014)
Background: Artemisia dracunculus L. belongs to the Anthemideae tribe of Asteraceae family. This plant has been used in traditional folk medicine. Also, itchr('39')s anti-bacterial, anti-fungal, antioxidant, anti-inflammatory and hepatoprotective activity has been proved. Objective: The purpose of this study was to evaluate the antioxidant activity of leaves and inflorescence of A. dracunculus and also to identify its phenolic compounds. Methods: A. dracunculus was collected in inflorescenceing season from Urmia. In this study, phenolic and flavonoid content, and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity for methanol extracts of leaves and inflorescences of A. dracunculus were investigated. Also, phenolic compounds were determined and measured by high performance liquid chromatography (HPLC). Results: Phenolic content of methanolic extracts of inflorescence of the A. dracunculus showed higher values than leaves. The highest flavonoid content was determined in leaves. There was a positive correlation between total phenolic content and the percentage of DPPH radical scavenging. Based on the results of the HPLC, seven phenolic compounds were detected in leaves and inflorescences (gallic acid, p-hydroxy benzoic acid, vanillic acid, p-coumaric acid, syrinjic acid, ferolic acid, sinapic acid). Conclusion: A. dracunculus contained phenolic compounds and showed significant antioxidant activity. High performance liquid chromatography results indicated significant differences (p<0.05) between different parts in case of phenolic compounds.